Wildsmith & Armitage's principles and practice of regional anaesthesia - McLeod, Graeme A.; McCartney, Colin J. L.; Wildsmith, J. A. W.; Elliott, Patrick (Illustrator); Crowe, Ken (Photographer) (Oxford : Oxford University Press, 2013)
The fourth edition of Wildsmith & Armitage's Principles and Practice of Regional Anaesthesia provides a comprehensive, up-to-date resource on regional anesthesia, focusing on practical applications and theoretical foundations. It includes advancements in techniques like ultrasound-guided anesthesia, alongside traditional methods. The chapters cover regional anesthesia for specific surgeries, patient groups like the elderly, and evolving practices for pain management. Edited by Graeme McLeod, Colin McCartney, and Tony Wildsmith, it is an essential reference for anesthetists seeking practical insights and clinical relevance in this specialty
Part 1: General Principles -- 1: History and development of local anaesthesia, Tony Wildsmith -- 2: Anatomy and physiology of pain, Lesley Colvin -- 3: The potential benefits, Nick Scott -- 4: Neurological complications, Colin McCartney -- 5: Outcome issues, Susan Nimmo & Graeme McLeod -- 6: Peripheral nerve and local anaesthetic drugs, Cameron Weir & Gary Strichartz -- 7: Local anaesthetic kinetics, Jenny Porter & Geoff Tucker -- 8: Drug Toxicity and selection, Nigel Bedforth & Jonathan Hardman -- 9: Preoperative considerations, Matthew Checketts -- 10: Peripheral nerve location techniques, George Corner & Calum Grant -- 11: Principles of patient management, Barrie Fischer -- Part 2: Anatomy and Techniques -- 12: Anatomy and physiology of vertebral canal, Ian Parkin & Alastair Chambers -- 13: Spinal anaesthesia, Jonathan Whiteside & Tony Wildsmith -- 14: Epidural block, Graeme McLeod -- 15: Sacral epidural (caudal) block, Edward Doyle & Jon McCormack -- 16: Regional anaesthesia of the trunk, John McDonnell & Dominic Harmon -- 17: Upper limb blocks, David Coventry -- 18: Lower limb blocks, Colin McCartney -- 19: Head, neck and airway blocks, Neil Smart, Stephen Hickey & Alistair Nimmo -- 20: Ophthalmic regional anaesthesia, Hamish McLure -- 21: Regional anaesthesia in obstetrics, Catriona Connolly & John McClure -- 22: Regional anaesthesia in children, Steve Roberts -- 23: Pain and autonomic blocks, Mick Serpell & Andreas Goebel -- 24: Regional anaesthesia for day-care surgery, Stuart Grant -- 25: Regional anaesthesia in the elderly, Bernadette Veering
Includes bibliographies and index.
Keywords: Conduction anesthesia; Anesthesia, Conduction